Konservasi Tanah dan Air di Perkebunan Kelapa Sawit Desa Wawolemo Kabupaten Konawe Demi Pembangunan yang Berkelanjutan - Alam, Syamsu; Hemon, M Tufaila; Suleman, Darwis; Leomo, Sitti; Yusuf, Dewi Nurhayati; Rustam, La Ode; Fatimah, Sitti; Perkasa, Muh. Alwis Arya; Kusumawati, Anna (Kadiri University, 2024)
Soil and water conservation efforts continue to be encouraged, considering the increasing number of openings of oil palm plantations that occur in various regions, including Wawolemo Village Konawe Regency. Clearing new land for oil palm planting is generally carried out by land clearing, which has the potential to cause erosion, so soil and water conservation efforts are needed to prevent land degradation, especially the loss of nutrients in the topsoil layer due to erosion. This community service activity aims to provide the community in Wawolemo Village with an understanding of the importance of soil and water conservation. Activities carried out in January 2024 for the farmers/community of Wawolemo Village. The method used was in the form of lectures or counseling and evaluation, where questionnaires were filled out before and after the activity took place. The results of the activity showed that there was an increase in the understanding and insight of the Wawolemo Village community after being provided with education, especially about erosion, soil, and water conservation techniques, as well as environmentally friendly and sustainable palm oil plantation practices based on soil and water conservation. By implementing a soil and water conservation system, smallholder oil palm growers are also expected to be able to save on fertilizer costs, which have been considered quite large, in order to obtain optimal production. Upaya konservasi tanah dan air terus digalakkan mengingat semakin banyaknya pembukaan kebun kelapa sawit yang terjadi di berbagai daerah, tidak terkecuali Desa Wawolemo Kabupaten Konawe. Pembukaan lahan baru untuk penanaman kelapa sawit umumnya dilakukan dengan cara land clearing yang berpotensi menyebabkan erosi, sehingga diperlukan upaya konservasi tanah dan air untuk mencegah terjadinya degradasi lahan terutama hilangnya unsur hara pada lapisan tanah atas karena erosi. Kegiatan pengabdian kepada masyarakat ini bertujuan memberikan pemahaman kepada masyarakat di Desa Wawolemo tentang pentingnya konservasi tanah dan air. Kegiatan dilakukan pada bulan Januari 2024 pada petani/masayarakat Desa Wawolemo. Metode yang digunakan berupa ceramah atau penyuluhan dan evaluasi dengan mengisi kuesioner sebelum dan sesudah kegiatan berlangsung. Hasil kegiatan menunjukkan terjadi peningkatan pemahaman dan wawasan masyarakat Desa Wawolemo setelah diberikan penyuluhan terutama tentang erosi, teknik konservasi tanah dan air, serta praktik perkebunan kelapa sawit yang ramah lingkungan dan berkelanjutan berbasis konservasi tanah dan air. Dengan penerapan sistem konservasi tanah dan air, pekebun sawit rakyat juga diharapkan dapat berhemat dari biaya pemupukan yang selama ini dianggap cukup besar untuk mendapatkan produksi yang optimal.